2014
DOI: 10.5935/0103-507x.20140042
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of intensive care professionals about diarrhea

Abstract: Objective To assess the opinions and practices of intensive care professionals with regard to diarrhea in critically ill patients.Methods A multicenter cross-sectional study was conducted among health care professionals working at three adult intensive care units. Participants responded individually to a self-administered questionnaire about their length of work experience in intensive care; the definition, characterization, and causes of diarrhea; types of records in the patient's medical record; and training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Children who require nutrition support from feeding tubes routinely report feeding intolerances. 4 Our national multicenter, retrospective study found that children who had switched to an "enteral formula with food-derived ingredients" reported a significant improvement in gastrointestinal symptoms, including a reduction in retching, flatulence, and vomiting. Dietitians reported clinical improvements within the first week of switching to the new enteral formula that were sustained throughout the study period.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Children who require nutrition support from feeding tubes routinely report feeding intolerances. 4 Our national multicenter, retrospective study found that children who had switched to an "enteral formula with food-derived ingredients" reported a significant improvement in gastrointestinal symptoms, including a reduction in retching, flatulence, and vomiting. Dietitians reported clinical improvements within the first week of switching to the new enteral formula that were sustained throughout the study period.…”
Section: Discussionmentioning
confidence: 97%
“…3 The frequency of diarrhea in enterally fed patients ranges from 29% to 72%. 4,5 The management of persistent feed intolerances results in repeated feed withdrawal to allow for gut rest, contributing to malnutrition through a reduction in nutrition intake, a decrease in nutrient absorption, and an increase in nutrient reserve catabolism. 6 In the pediatric population interest is growing in the use of a blended diet for the management of feeding intolerances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite all pre-cautions, intestinal bowel material is "differentially diluted" among different patients, due to case dependent differential "biomass wash-outs", during presentation of acute diarrheal symptoms, the total bacterial load could vary up to few log values [3]. Whenever pre-analytical sampling variability is large [1,2,[4][5][6][7][8] and quantification is intended to establish the clinical status of the patient, normalization based on sample mass, or sample volume is not effective.…”
Section: Introductionmentioning
confidence: 99%
“…Lordani et al(2014) mostram que dentre os fatores adversos mais corriqueiros que podem influenciar a descontinuidade da referida terapia são: resíduos gástricos excessivos, distensão abdominal, náuseas/vômitos, diarréia, constipação, doenças gastrointestinais, uso de sedação, opióides,…”
unclassified